Badanie współzależności cen transakcyjnych na lokalnych segmentach rynku nieruchomości na potrzeby określania wartości rynkowej nieruchomości w przypadkach szczególnych - Pawlukowicz, Roman (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
It often occurs that it is unfeasible to determine property market value in the way set by legal regulations and professional standards. The obstacle to it is usually the lack of transactions of properties comparable to the property under appraisal in the market relevant according to the location of the property being appraised. The above situation commonly applies in the appraisal of undeveloped land properties being the subject of the right of property (perpetual usufruct) situated in central areas of most cities in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 372-382